Understanding inequalities in the coverage of adolescent sexual and reproductive health services: a qualitative case study of the selected regions of Zambia - Munakampe, Margarate Nzala; Ngoma-Hazemba, Alice; Sampa, Mutale; Jacobs, Choolwe N. (Frontiers in Reproductive Health, 2024)
IntroductionDespite substantial investment in improving healthcare among adolescents in low- and middle-income countries, barriers to access and utilization of services persist, especially to sexual and reproductive health (SRH) services. In response to adolescents' health service needs due to their vulnerability, interventions aimed at improving access and utilization of sexual and reproductive health services have been implemented in specific regions of Zambia. To highlight progress in the access and the overall delivery of services in Zambia, in the wake of a system-level funding mechanism, this paper aims to understand the accessibility, availability, acceptability and quality (AAAQ) of health services provided to young people.Materials and methodsIn a qualitative case study, 48 discussions- 32 individual interviews with stakeholders and 16 focus group discussions, consisting of 128 male and female adolescents were conducted in six districts from Eastern, Southern and Muchinga provinces of Zambia. Interviews were audio-recorded, recordings transcribed verbatim, and transcripts were analysed using deductive thematic analysis, using the AAAQ framework and Atun's framework on integration, as a guide to reporting the findings.ResultsWe found that adolescents knew of and had access to common commodities and services- male condoms, health education and HIV counselling and testing. However, availability was affected by access-related barriers such as frequent stock-outs and insufficiently trained healthcare providers. In addition, accessibility was more restricted during the COVID-19 pandemic lockdown and compounded by the low acceptability of SRH service among adolescents across all contexts. This led to the use of alternatives such as herbal medicine and maintained common myths and misconceptions. The overall quality was marred by the lack of dedicated spaces for adolescent health services and the lack of information, education and communication (IEC) materials in some spaces.ConclusionWhile it was noted that some services were available for adolescents in all the study sites, numerous barriers inhibited access to these services and had an impact on the quality-of-service provision. With the added restriction to SRH service asses for young people, due to the low acceptability of adolescent SRH service use, the overall integration of adolescent SRH interventions into routine service provision was low and can be improved by targeting contextual barriers and maintaining best practices.